Lessons From The Past The Du Jiang Yen-Chinas Ancient Irrication Project. - Kung, Hsiang-Te; Robinson, J B; Chan, Ngai Weng (USM, 2006)
Development of the Cheng-du Plain, an alluvial plain located in the central western part of China's Sichuan Province, exemplifies the harmonious interactions of man and nature.